Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1152/ajpheart.00594.2014
|View full text |Cite
|
Sign up to set email alerts
|

PC-PLC/sphingomyelin synthase activity plays a central role in the development of myogenic tone in murine resistance arteries

Abstract: Myogenic tone is an intrinsic property of the vasculature that contributes to blood pressure control and tissue perfusion. Earlier investigations assigned a key role in myogenic tone to phospholipase C (PLC) and its products, inositol 1,4,5-trisphosphate (IP3) and diacylglycerol (DAG). Here, we used the PLC inhibitor, U-73122, and two other, specific inhibitors of PLC subtypes (PI-PLC and PC-PLC) to delineate the role of PLC in myogenic tone of pressurized murine mesenteric arteries. U-73122 inhibited depolari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…Unlike P2ry6 −/− animals, P2ry2 −/− mice did not display altered MT (Figure IX in the online-only Data Supplement) highlighting a nonredundant role of P2Y 6 receptor in MT where intracellular calcium increase is minimally involved. 21 …”
Section: Discussionmentioning
confidence: 99%
“…Unlike P2ry6 −/− animals, P2ry2 −/− mice did not display altered MT (Figure IX in the online-only Data Supplement) highlighting a nonredundant role of P2Y 6 receptor in MT where intracellular calcium increase is minimally involved. 21 …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, studies in fourth-order murine mesenteric arteries found no role for IP 3 and IP 3 Rs in myogenic tone (966). Instead, they propose that PLC hydrolyzes phosphatidylcholine to produce DAG that is essential for myogenic tone in this murine resistance artery (966). …”
Section: Inositol-145-triphosphate Receptorsmentioning
confidence: 99%
“…In murine mesenteric resistance arteries it was also shown that block of IP 3 Rs with xestospongin C had no effect on myogenic tone (966). Thus, in these vessels IP 3 Rs do appear to contribute to myogenic tone.…”
Section: Inositol-145-triphosphate Receptorsmentioning
confidence: 99%
“…Pharmacological inhibition of IP 3 R can be achieved with the application of widely used agents such as 2-APB and xestospongin C. IP 3 R inhibition may have distinct effects on vascular reactivity. For instance, in mouse mesenteric arteries, IP 3 R inhibition with xestospongin C did not affect the myogenic tone, but did prevent the phenylephrine-induced vasoconstriction (Mauban, Zacharia, Fairfax, & Wier, 2015). IP 3 R activity in VSM can be modulated by [Ca 2+ ] i , luminal SR Ca 2+ load, ATP, several protein kinases (e.g., PKA, PKG), regulatory proteins (e.g., RACK, FKBP12), reactive oxygen species (ROS), and pH (Bezprozvanny, Watras, & Ehrlich, 1991; Iino, 1990; Narayanan et al, 2012).…”
Section: Sr Ca2+ Channelsmentioning
confidence: 99%